KEBIJAKSANAAN LEMBAGA KETAHANAN NASIONAL (LEMHANNAS) DALAM PENGUATAN IDEOLOGI BERDASARKAN 4 DASAR KONSENSUS NEGARA - Mayasari, Ragil Ira; Khusumawati, Titik; Swandana, Irwan; Rahmanto, Lucius Andik (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2024)
One aspect of the goal of national education is to form human beings who have noble ethics. The 2021 Virtual Training on Strengthening National Values (TAPLAI) is one of the government's efforts through the National Resilience Institute (Lemhannas) in strengthening national values. The purpose of the Virtual Training on Strengthening National Values (TAPLAI) is to overcome existing differences and problems through comprehensive, integral, and holistic mindsets, attitudes, and actions, in order to maintain the integrity of the Republic of Indonesia. Indonesia, which has an ideology based on the Four Foundations of the Unity of the Republic of Indonesia (the 1945 Constitution, Pancasila, the Republic of Indonesia, and Sesanti Bhinneka Tunggal Ika), has a strong national insight. This study uses a normative legal research method with a legislative approach, namely studying and understanding laws and regulations and understanding the implications of positivizing the general principles of good governance in the administration of government. This research also uses a conceptual approach, namely looking for principles, principles and doctrines related to this research. This scientific activity is not based on a review of one discipline, but the perspective of an educational discipline. However, this research is still a legal research. This refers to the perspective of the legal discipline used in its implementation. The 2021 Virtual Training for Strengthening National Values (TAPLAI) which was held for ± 10 days obtained significant results, namely an increase of 913 points and an average of 12.17 in the sense of "very satisfied" in building a sense, understanding, and enthusiasm to implement national values sourced from the Four Basic Consensuses of Indonesia in their respective environments.